Molly's Surprise: A Christmas Story - Tripp, Valerie (Pleasant Company Publications Incorporated, 1986)
Even though he is away serving in an English hospital during World War II, Molly's father finds a way to make the family Christmas very special.
Keywords: Social Issues; General; Juvenile Nonfiction